Fractional CO2 Laser in the Treatment of Post-Menopausal Vaginal Atrophy Fractional CO2 Laser in Post-Menopausal Women (Global Journal of Medical Research, 2022)
Introduction Similarly to other parts of the body the vagina changes over time and vaginal atrophy is a common condition in women between 45 and 55 years of age It causes discomfort and psychological suffering in addition to being the main cause of pain during sexual intercourse Objective This study aimed to evaluate the use of intravaginal fractional CO2 laser in the treatment of atrophy of the vaginal mucosa as well as its effect on symptoms such as itching irritation pain dyspareunia urinary incontinence dryness and loss of mucosal elasticity Methods This is a prospective cohort of 14 menopausal women with vulvovaginal symptoms who were evaluated pre- and post-procedure with CO2 laser treatment using the Monalisa Touch technique Cytological examination and validated questionnaires were used in the assessment
Keywords: vaginal atrophy; vaginal rejuvenation; fractional CO2 laser